2020
DOI: 10.1007/s11230-020-09919-3
|View full text |Cite
|
Sign up to set email alerts
|

Steringophorus merretti n. sp. (Digenea: Fellodistomidae) from the deep-sea fish Cataetyx laticeps Koefoed (Ophidiiformes: Bythitidae) from the Goban Spur, Northeastern Atlantic Ocean

Abstract: A new species of deep-sea digenean, Steringophorus merretti n. sp., is described from the bythitid fish Cataetyx laticeps in deep waters of the Goban Spur, Northeastern Atlantic. It is distinguishable from other described members of the genus by its tiny eggs and large cirrus-sac. A phylogenetic tree, based on 28S rDNA sequences, indicates that this species is embedded within a clade of deep-sea species and is sister to the eurybathic species S. thulini Bray & Gibson, 1980. Steringotrema robertpoulini Pérez-Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…On the other hand, Pérez-Ponce de León et al (2018) added Steringotrema robertpoulini Pérez-Ponce de León, Anglade & Randhawa, 2018 from a shallow water pleuronectid to the phylogeny, finding it a sister species to S. dorsolineatus ( Reimer, 1985 ) from deep sea ipnopids, which together form a clade sister to the remaining members of Steringophorus . Bray and Waeschenbach (2020) produced a phylogenetic tree which also placed Steringotrema robertpoulini within the genus Steringotrema , but not as sister to S. dorsolineatus . They found that the family divided distinctly into two well supported clades, one of parasites of shallow and warm water fishes and the other of deep-sea or cold-water fishes, with the pattern spoiled by the position of Steringotrema robertpoulini .…”
Section: Phylogenymentioning
confidence: 99%
“…On the other hand, Pérez-Ponce de León et al (2018) added Steringotrema robertpoulini Pérez-Ponce de León, Anglade & Randhawa, 2018 from a shallow water pleuronectid to the phylogeny, finding it a sister species to S. dorsolineatus ( Reimer, 1985 ) from deep sea ipnopids, which together form a clade sister to the remaining members of Steringophorus . Bray and Waeschenbach (2020) produced a phylogenetic tree which also placed Steringotrema robertpoulini within the genus Steringotrema , but not as sister to S. dorsolineatus . They found that the family divided distinctly into two well supported clades, one of parasites of shallow and warm water fishes and the other of deep-sea or cold-water fishes, with the pattern spoiled by the position of Steringotrema robertpoulini .…”
Section: Phylogenymentioning
confidence: 99%